The novel and taxonomically restricted Ah24 gene from grain amaranth (Amaranthus hypochondriacus) has a dual role in development and defense - Massange-Sanchez, Julio A.; Palmeros-Suarez, Paola A.; Martinez-Gallardo, Norma A.; Castrillon-Arbelaez, Paula A.; Aviles-Arnaut, Hamlet; Alatorre-Cobo, Fulgencio; Tiessen, Axel; Délano-Frier, John P. (Frontiers in Plant Science, 2015)
Grain amaranths tolerate stress and produce highly nutritious seeds. We have identified several (a)biotic stress-responsive genes of unknown function in Amaranthus hypochondriacus, including the so-called Ah24 gene. Ah24 was expressed in young or developing tissues; it was also strongly induced by mechanical damage, insect herbivory and methyl jasmonate and in meristems and newly emerging leaves of severely defoliated plants. Interestingly, an in silico analysis of its 1304 bp promoter region showed a predominance of regulatory boxes involved in development, but not in defense. The Ah24 cDNA encodes a predicted cytosolic protein of 164 amino acids, the localization of which was confirmed by confocal microscopy. Additional in silico analysis identified several other Ah24 homologs, present almost exclusively in plants belonging to the Caryophyllales. The possible function of this gene in planta was examined in transgenic Ah24 overexpressing Arabidopsis thaliana and Nicotiana tabacum plants. Transformed Arabidopsis showed enhanced vegetative growth and increased leaf number with no penalty in one fitness component, such as seed yield, in experimental conditions. Transgenic tobacco plants, which grew and reproduced normally, had increased insect herbivory resistance. Modified vegetative growth in transgenic Arabidopsis coincided with significant changes in the expression of genes controlling phytohormone synthesis or signaling, whereas increased resistance to insect herbivory in transgenic tobacco coincided with higher jasmonic acid and proteinase inhibitor activity levels, plus the accumulation of nicotine and several other putative defense-related metabolites. It is proposed that the primary role of the Ah24 gene in A. hypochondriacus is to contribute to a rapid recovery post-wounding or defoliation, although its participation in defense against insect herbivory is also plausible.